Network Administration & Management - Yusof, R.; Abdollah, M. F.; Sahib, S. (Venton Publishing, 2007)
The objective of this module is to expose the student to network administration and management environment by using variety tools and network devices. The task will involve the setup configuration of the network. These tools will help student in understanding and applying the network administration and management areas and processes. Each lab offers student many opportunities to get hands-on and build new network administration and management tools skills.